The development of teaching materials based on mathematical modeling in the context of climate change for prospective teachers - Agustarina, Mitta; Hiltrimartin, Cecil; Aisyah, Nyimas; Ismet, Ismet; Meilinda, Meilinda; Silvhiany, Sary (Universitas Islam Raden Intan Lampung, INDONESIA, 2022)
Mathematical modeling ability is one of the important skills prospective teachers and students possess in solving contextual problems. One that often happens around us is climate change. This study aims to develop teaching materials based on mathematical modeling in the context of climate change that is valid and practical. The method used is research and development with the ADDIE development model. This research was conducted at one of the state universities in Indonesia with a total of 53 subjects. Data collection techniques using observation, interviews, and tests. Data analysis techniques use qualitative research methods by looking at indicators and mathematical modeling abilities. This research produces teaching material based on mathematical modeling in the context of climate change that is valid and practical for prospective teachers. The evaluation results showed that most of the research subjects could not solve the problems correctly. Teaching materials based on mathematical modeling that have been developed can be input for prospective teachers regarding teaching materials that will be given, especially in the context of climate change, so that later they will help develop students' problem-solving abilities.